ANALISIS LINGKUNGAN SEKOLAH, KEMAMPUAN PEDAGOGIK DAN TUNJANGAN TERHADAP KUALITAS DIDIK PADA SMAN UPT WILAYAH 1 MAKASSAR - Uluputty, Nurdjanna Fadjrin; Sabil, Marhaeni (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
This study aims to analyze the effect of the school environment, pedagogic ability and allowances on teacher quality and analyzed by single regression. While the analysis of the influence of the school environment, pedagogic ability and allowances simultaneously affect the quality of teachers, it is analyzed multiple regressions. This research was conducted for one year, from January to December 2020, which is located at the UPT Region State Senior High School. Region 1 Makassar. This study uses primary and secondary data. Data collection techniques used were observation and interviews. The population of this research is the teachers of SMA Negeri UPT Wilayah 1 Makassar. The research sample was taken 100 teachers. The teacher sample was taken proportionally with the proportional random sampling method. Data processing was performed using tabulations and percentages. The analysis used is quantitative data analysis, single regression and multiple regression using a Likert scale obtained from a list of questions classified into five levels. The results showed that (1) the influence of the school environment on the quality of students was not significant or had no significant impact (2) the effect of teacher pedagogy on the quality of students had a positive and significant effect (3). the effect of the certification allowance on the quality of students has a positive and significant effect.